Late glacial summer paleohydrology across Central Europe - Prochnow, Maximilian; Hepp, Johannes; Strobel, Paul; Zech, Roland; Acharya, Sudip; Szidat, Sönke; Rius, Damien; Millet, Laurent; Glaser, Bruno; Zech, Michael (2024)
It is generally accepted that a weakening of the North Atlantic thermohaline circulation caused the Younger Dryas cooling. Although the role of seasonality was emphasized previously, this aspect is rarely considered yet, and it remains elusive how this impacted hydroclimate during winters and summers across Central Europe. Here, we coupled biomarker-based δ18O and δ2H from Bergsee in southern Germany to reconstruct deuterium excess as a proxy for evaporation history from the Bølling-Allerød to the Preboreal. We compared this dataset with other biomarker isotope records in Central Europe. They are all lacking a strong isotopic depletion during the Younger Dryas, which is best explained by the summer sensitivity of the biomarker proxies: As Younger Dryas summers were relatively warm, there is an absence of the strong winter cooling signals recorded in annual water isotope records like Greenland or Lake Steißlingen. Lake evaporation at Bergsee together with other paleohydrological reconstructions draw a coherent picture of the Late Glacial hydroclimate, with strong evidence for warm and dry Younger Dryas summers. Rather than a southward shift of the Westerlies during winter, we suggest that a recently proposed feedback mechanism between North Atlantic sea ice extend, strong winter cooling and summer atmospheric blocking serves as a suitable explanation for summer dryness. Additional confidence to the robustness of these biomarker records is provided by the overall agreement of paleohydrological fluctuations during the Preboreal.